PENGARUH PERPUTARAN MODAL TERHADAP HASIL PENJUALAN WARUNG SERBA ADA (WASERDA) DI KOPERASI UNIT DESA MANDIRI JAYA MAKMUR DESA BANJAR JAYA - Nende Rahmawati; Pratiwi Indah Sari (Universitas Batanghari Jambi, 2020)
This study aims to determine the turnover of capital to the sale of Multipurpose Stalls (WASERDA) in the Cooperative Unit Desa Mandiri Jaya Makmur Desa Banjar Jaya. From the results of the t test analysis, it is known that there is a significant effect on the variable (X) capital turnover and variable (Y) sales results. This is evidenced by the results of the t test calculation of 5.539, while the t table is 1.684 at the 5% significance level, which means that Ha is accepted. Thus, it can be concluded that for both large, medium and small profit institutions, the turnover of capital has an impact on the smooth running of business in the future. This is because capital is the same as an important part that flows all activities to various sectors and scales so that they can run properly, and in the end will increase economic growth for both institutions and human resources in it.